Infants and adults reaching in the dark. - Babinsky, E; Braddick, O; Atkinson, J (2012)
It has been shown that infants over the age of 6 months will reach for an object in complete darkness. This experiment measured the reaching movements of 9- to 16-month-old infants and adults under several different conditions of illumination to investigate the role of vision and stored visual representations in reach control. In one condition, participants reached for an object with the lights on. In a second condition, participants reached for an object glowing in the dark (glowing condition). This allowed us to measure the effects of vision of the arm and vision of the reach space. We also looked at the effect of removing vision of the object on reach control: in the final two conditions, participants reached for an object in complete darkness (0-s dark) and in complete darkness after a 4-s delay (4-s dark). We compared the kinematics of a reach (e.g. average speed, reach straightness) between the four illumination conditions. The results showed that infants reached faster and decelerated for a shorter period of time in the dark (0- and 4-s dark) than in the light. By comparison, adults reached slower and decelerated for a longer period of time in the dark (0- and 4-s dark) than in the light. We did not find any effect of the glowing condition compared to full vision on infant reaching movements. These results suggest that infant reaching movements only become compromised when the target is not visible, whereas vision of the hand and the reach space are less significant. Without online visual feedback, an infant reach in the dark appears to be driven by feedforward mechanisms and control may be affected by an immature ability to form and/or retain visual spatial memory.